2022
DOI: 10.1101/2022.03.08.483433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The oxytocin system regulates tearing

Abstract: Tears are an exocrine physiological fluid secreted onto the ocular surface from the lacrimal apparatus in all mammals. Limited research has been conducted on the functional neuronal circuitry of tear production. In particular, the neuronal mechanisms of emotional tearing, which is a physiological reaction harmonized with enhanced emotional arousal and assumed to be unique to humans, remain unclear. We identified that the oxytocin neurons in the paraventricular hypothalamus is functionally projected to the oxyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In this study, we found that tearing dog face can facilitate human caring emotion to dogs, which is similar function observed in human children. We also discovered that emotional tear can be also observed in mice, maternal reunion, nociceptive stimulation, and aversive memory retrieval are linked to tearing in mice 14 . The social function of tearing in animals needs to be elucidated in future.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In this study, we found that tearing dog face can facilitate human caring emotion to dogs, which is similar function observed in human children. We also discovered that emotional tear can be also observed in mice, maternal reunion, nociceptive stimulation, and aversive memory retrieval are linked to tearing in mice 14 . The social function of tearing in animals needs to be elucidated in future.…”
Section: Discussionmentioning
confidence: 74%
“…Recently we discovered the OXT can facilitated the synthesis and release of tears in the mouse brain; OXT neurons located in the paraventricular hypothalamus send the fibers to the superior salivary nucleus and increase the tear secretion. Therefore, OXT increase during the reunion with the owner can act on both central and peripheral organs to stimulate tear secretion 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in mice demonstrated that oxytocin neurons located in the paraventricular hypothalamus send fi bers to the superior salivary nucleus and are involved in increasing tear production. Therefore, oxytocin increase related to positive and negative emotional arousal can facilitate tear secretion, acting on both central and peripheral organs 7 . One point to note is that oxytocin administration also acts on vasopressin receptors, so it will be necessary to clarify in the future which receptors were affected by the results of this administration experiment.…”
Section: Correspondencementioning
confidence: 99%